A Business Plan for PK Handbags Manufacturing Company - Somchatvong, Laddaporn (2009)
PK Co. Limited is a small family-business-owned company located in Thailand. Since established in 1998, the company’s business is manufacturing women’s fashion handbags for wholesale apparel trading company in Thailand. The company also produces and merchandises premium gifts for Kasikorn Bank, one of the largest banks in Thailand. Over the past ten years, the company has generated more than 200 million Baht in revenue or £ 3.6 million . The founders, Likit and Duangporn Somchatvong, have more than thirty year experience in handbags, leather and shoes industry. They have gained good reputation and valuable connections during three decades in the business. As a result, the company has been contacted to be one of handbags suppliers for Macro and Tesco-Lotus, one of the largest retail stores in Thailand. The potential orders from them would triple number of orders that the company receives at present. However, with current production capacity, the company will not be able to supply as many as demanded. Therefore, the company needs an investment to expand the production capacity. The plan is to construct and develop another factory in Thailand, potentially in ChiangRai province. In addition, the company is planning to focus more on premium gifts industry as there is high potential of growth in the market. We are looking for an investment of 2 million Baht for the offer of 20% of our equity. The investor will receive 20,000 ordinary shares (100 Baht/Share), during five years of agreement period. It is estimated that the new factory will generate approximately 9 million Baht in revenue in 2010 and will dramatically increase to 45 million Baht in 2013. Payback period for 2 million Baht initial investment will be within three years. As a family owned business moving to operate larger and more structured factory, we will not only seek for the investment, but also support and advice on management from the investor.